Don't Let Go - Bussi, Michel (London Weidenfeld & Nicolson, 2017)
From the bestselling author of AFTER THE CRASH ('a novel so extraordinary it reminded me of reading Stieg Larsson for the first time' Sunday Times): a man's wife goes missing. He didn't kill her so why is he so guilty?
Keywords: Fugitives from justice -- Missing persons -- Family vacations